S100A8/A9 is not involved in host defense against murine urinary tract infection. - Mark C Dessing; Loes M Butter; Gwendoline J Teske; Nike Claessen; Chris M van der Loos; Thomas Vogl; Johannes Roth; Tom van der Poll; Sandrine Florquin; Jaklien C Leemans (PLoS ONE, 2010)
BACKGROUND: Inflammation is commonly followed by the release of endogenous proteins called danger associated molecular patterns (DAMPs) that are able to warn the host for eminent danger. S100A8/A9 subunits are DAMPs that belong to the S100 family of calcium binding proteins. S100A8/A9 complexes induce an inflammatory response and their expression correlates with disease severity in several inflammatory disorders. S100A8/A9 promote endotoxin- and Escherichia (E.) coli-induced sepsis showing its contribution in systemic infection. The role of S100A8/A9 during a local infection of the urinary tract system caused by E. coli remains unknown. METHODOLOGY/PRINCIPAL FINDINGS: We investigated the contribution of S100A8/A9 in acute urinary tract infection (UTI) by instilling 2 different doses of uropathogenic E. coli transurethrally in wild type (WT) and S100A9 knockout (KO) mice. Subsequently, we determined bacterial outgrowth, neutrophilic infiltrate and inflammatory mediators in bladder and kidney 24 and 48 hours later. UTI resulted in a substantial increase of S100A8/A9 protein in bladder and kidney tissue of WT mice. S100A9 KO mice displayed similar bacterial load in bladder or kidney homogenate compared to WT mice using 2 different doses at 2 different time points. S100A9 deficiency had little effect on the inflammatory responses to E. Coli-induced UTI infection, as assessed by myeloperoxidase activity in bladder and kidneys, histopathologic analysis, and renal and bladder cytokine concentrations. CONCLUSIONS: We show that despite high S100A8/A9 expression in bladder and kidney tissue upon UTI, S100A8/A9 does not contribute to an effective host response against E. Coli in the urinary tract system.